2002
DOI: 10.1074/jbc.c200418200
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Mitogen-activated Protein Kinase-activated Protein (MAPKAP) Kinase 2 Suggests a Bifunctional Switch That Couples Kinase Activation with Nuclear Export

Abstract: MAPK-activated protein kinase 2 (MAPKAPK2), one of several kinases directly phosphorylated and activated by p38 MAPK, plays a central role in the inflammatory response. The activated MAPKAPK2 phosphorylates its nuclear targets CREB/ATF1, serum response factor, and E2A protein E47 and its cytoplasmic targets HSP25/27, LSP-1, 5-lipoxygenase, glycogen synthase, and tyrosine hydroxylase. The crystal structure of unphosphorylated MAPKAPK2, determined at 2.8 Å resolution, includes the kinase domain and the C-termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
112
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(118 citation statements)
references
References 30 publications
5
112
0
Order By: Relevance
“…Mutation of both Thr 344 and the T-loop phosphorylation site in MAPKAPK2 to acidic residues resulted in a kinase that is constitutively active [34,35]. In combination with structural information from crystallographic studies [36,37] this has suggested a model for MAPKAPK2 activation in which phosphorylation of Thr 334 promotes the dissociation of an autoinhibitory C-terminal helix from the substrate-binding groove of the kinase domain, while phosphorylation of the activation loop on Thr 222 stabilizes its structure and promotes substrate binding [35,37].…”
Section: Discussionmentioning
confidence: 99%
“…Mutation of both Thr 344 and the T-loop phosphorylation site in MAPKAPK2 to acidic residues resulted in a kinase that is constitutively active [34,35]. In combination with structural information from crystallographic studies [36,37] this has suggested a model for MAPKAPK2 activation in which phosphorylation of Thr 334 promotes the dissociation of an autoinhibitory C-terminal helix from the substrate-binding groove of the kinase domain, while phosphorylation of the activation loop on Thr 222 stabilizes its structure and promotes substrate binding [35,37].…”
Section: Discussionmentioning
confidence: 99%
“…Other hydrophobic residues and, in particular, isoleucine, may replace the leucines. Some NESs have been recognized to have a specific secondary structure, with a portion of the NES residing on an ␣-helix and a portion extending onto an adjacent random coil (39,40). This structure is found in NESs from p53, IB␣, MAPK-activated protein kinase (MK)-2 and 14 -3-3.…”
mentioning
confidence: 99%
“…Among the targets of p38 is MAPK-kinase 2 (MKK2). Its phosphorylation at T317 allows MKK2 nuclear export in a complex containing p38 itself (Meng et al, 2002). Phosphorylation of heat shock protein 27 (HSP27), a substrate of MKK2, is increased in skeletal muscle hypertrophy and decreased during atrophy (Huey, 2006;Kawano et al, 2007), while HSP27…”
Section: Strategies To Correct Metabolic Alterationsmentioning
confidence: 99%